Outcomes Following Hypofractionated Stereotactic Radiotherapy to the Cavity After Surgery for Melanoma Brain Metastases. Issue 3 (March 2022) - Gallo, J.; Garimall, S.; Shanker, M.; Castelli, J.; Watkins, T.; Olson, S.; Huo, M.; Foote, M.C.; Pinkham, M.B.
Abstract: Aims: Hypofractionated stereotactic radiotherapy (HSRT) to the cavity after surgical resection of brain metastases improves local control. Most reported cohorts include few patients with melanoma, a population known to have high rates of recurrence and neurological death. We aimed to assess outcomes in patients with melanoma brain metastases who received HSRT after surgery at two Australian institutions. Materials and methods: A retrospective analysis was carried out including patients treated between January 2012 and May 2020. HSRT was recommended for patients with melanoma brain metastases at high risk of local recurrence after surgery. Treatment was delivered using appropriately commissioned linear accelerators. Routine follow-up included surveillance magnetic resonance imaging brain every 3 months for at least 2 years. Primary outcomes were overall survival, local control, incidence of radiological radionecrosis and symptomatic radionecrosis. Results: There were 63 cavities identified in 57 patients. The most common HSRT dose prescriptions were 24 Gy in three fractions and 27.5 Gy in five fractions. The median follow-up was 32 months in survivors. Local control was 90% at 1 year, 83% at 2 years and 76% at 3 years. Subtotal brain metastases resection (hazard ratio 12.5; 95% confidence interval 1.4–111; P = 0.0238) was associated with more local recurrence. Overall survival was 64% at 1 year, 45% at 2 years and 40% at 3 years. There were 10 radiological radionecrosis events (16% of cavities) during the study period, with 5% at 1 year and 8% at 2 years after HSRT. The median time to onset of radiological radionecrosis was 21 months (range 6–56). Of these events, three became symptomatic (5%) during the study period at a median time to onset of 26 months (range 21–32). Conclusion: Cavity HSRT is associated with high rates of local control in patients with melanoma brain metastases. Subtotal resection strongly predicts for local recurrence after HSRT. Symptomatic radionecrosis occurred in 5% of cavities but increased to 8% of longer-term survivors. Highlights: 63 cavities from patients with melanoma brain metastases received radiation after surgery. Local control was 83% at 2 years. The rate of symptomatic radionecrosis was 5%. Subtotal resection was associated with higher rates of local recurrence.